66.4k views
1 vote
Solve by elimination.
5x - 6y = 27
7x + 6y = 9
Show work pls

1 Answer

5 votes

Answer:

x = 3

y = - 2

Explanation:

5x - 6y = 27 .......... Equation 1

7x + 6y = 9 ………… Equation 2

To solve using elimination add the second equation to the first one to eliminate y

That's

5x - 6y + 7x + 6y = 27 + 9

12x + 6y - 6y = 36

12x = 36

Divide both sides by 12

x = 3

Substitute it into any of the equations

Using equation 2

That's

7(3) + 6y = 9

21 + 6y = 9

6y = - 12

Divide both sides by 6

y = - 2

The solutions are

x = 3

y = - 2

Hope this helps you

User Runonthespot
by
5.6k points